Anorectal function in patients with complete supraconal spinal cord lesions. - MacDonagh, R (1992)
Anorectal manometry and sphincter electromyography were performed in 23 patients with complete supraconal traumatic spinal injuries and 30 age and sex matched control subjects. Basal pressures in the spinal group were similar to those in normal subjects but conscious control of sphincter activity was abolished in all spinal patients. Discriminant rectal sensation was also abolished during rectal distension, but 40% of patients experienced a dull pelvic ache at maximum levels of distension. Phasic rectal contraction and anal relaxation were present but exaggerated and induced at lower distending volumes than in normal subjects. The configuration of the rectal pressure/volume relationship was linear in patients compared with a reversed 'S' shape in normal subjects. The external anal sphincter response to rectal distension was noticeably attenuated, reinforcing the view that this spinal reflex is heavily modulated by supraspinal centres under normal circumstances. The external anal sphincter response to increases in abdominal pressure was also attenuated, and the anal pressures were strongly correlated with the level of the lesion and the abdominal pressure the patient could generate. No spinal patient showed a decrease in external anal sphincter activity during straining 'as if to defecate.' The exaggerated anorectal smooth muscle responses to rectal distension and the attenuated external sphincter response explain why patients with complete supraconal spinal lesions experience uncontrollable reflex defecation, while the persistance of external and sphincter contraction and the absence of any external anal sphincter relaxation during straining 'as if to defecate' might explain the difficulty that these patients have in consciously expelling rectal contents.